Romanesque renaissance : Carolingian, Byzantine and Romanesque buildings (800-1200) as a source for new all'antica architecture in early modern Europe (1400-1700) - Ottenheym, Koen (NIKI studies in Netherlandish-Italian art history, 2021)
"From the fifteenth century onwards scholars and architects investigated age-old buildings in order to look for useful sources of inspiration. They too, occasionally misinterpreted younger buildings as proofs of majestic Roman or other ancient glory, such as the buildings of the Carolingian, Ottonian and Stauffer emperors. But even if the correct age of a certain building was known, buildings from c. 800 - 1200 were sometimes regarded as 'Antique' architecture, since the concept of 'Antiquity' was far more stretched than our modern periodisation allows. This was a Europe-wide phenomenon. The results are rather diverse in style, but they all share an intellectual and artistic strategy: a conscious revival of an 'ancient' architecture- whatever the date and origin of these models"--